Polymer composites prepared from heat-treated starch and styrene–butadiene latex. (February 2016) - Kim, Sanghoon; Adkins, Jason; Aglan, Heshmat A; Biswas, Atanu; Selling, Gordon
Thermoplastic starch/latex polymer composites were prepared using styrene–butadiene latex and heat-treated cornstarch. The composites were prepared in a compression mold at 130°C, with 20% starch content. An amylose-free cornstarch, waxy maize, was used for this research, and the heat treatment range was from ambient temperature to 170°C. The heat-treated starch (HTS) was characterized by optical microscopy, dynamic light scattering, and size exclusion chromatography. The composites were characterized by mechanical analysis (stress–strain) and by scanning electron microscopy. The mechanical tests of composites revealed a dramatic increase in the modulus and tensile strength when the gelatinized starch was incorporated. When the starch was not gelatinized, starch did not contribute to the increase in the modulus and tensile strength because of its small surface area, thus weak interaction with the matrix. The reinforcing effect of starch as filler was reduced as the heating temperature of starch was increased to higher than 120°C. The variation of reinforcement effect of HTS as filler was explained by the interaction between starch and matrix material, latex.